A indústria de semicondutores: estratégias, inovações e tensões geopolíticas na era digital - Dias, João Pedro Pinto (Universidade Federal de São Carlos, 2025)
The semiconductor industry, since the invention of the transistor in the United States in 1947, has evolved to become one of the central pillars of the contemporary global economy and geopolitics. This study analyzes how historical factors uch as the Cold War and the space race drove technological advancement and the mass production of semiconductors, highlighting the role of Silicon Valley and pioneering companies like Fairchild, Texas Instruments, and Intel, as well as he revolution brought about by photolithography. The work explores the Asian ascent, initiated by Japan and consolidated through strategic policies in South Korea and Taiwan, culminating in the global leadership of TSMC, which, under the vision of Morris Chang and the "pure-play foundry"model, transformed Taiwan into the epicenter of advanced chip manufacturing, responsible for over 60% of global production and 90% of cutting-edge semiconductors. The analysis details the complex supply chain, marked by U.S. leadership in design, Asian dominance in manufacturing, and European supply of EUV machines—critical equipment for the most modern chip generations—and discusses how this interdependence underpins Taiwan’s "Silicon Shield,"granting it a strategic role in global geopolitics. Finally, the study addresses the vulnerabilities and tensions arising from the concentration of production in Taiwan, especially in the face of U.S.-China rivalry, demonstrating that control over semiconductors is now a determining factor for the balance of power in the 21st century.
The semiconductor industry: strategies, innovations, and geopolitical tensions in the digital age
Keywords: Semicondutores; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA::ESTADOS ELETRONICOS